Mental toughness' level differences between gender among marathon runners / Fatin Nurafiqah Mohd Fadzil - Mohd Fadzil, Fatin Nurafiqah (2019)
The main purpose of this study was to difference of mental toughness level between gender among marathon runners. Two hundred ninety eight (298) endurance runners were involved as respondent. The demographic profile form and Psychological Perfom1ance Inventory questionnaire were employed in the current study for data collection. The descriptive statistic of demographic profile based on gender (N=298) between female (N=1 41) and male (N=1 57). The result of this study on mental toughness level among endurance runners for low (N=l 17 or 39.3%), moderate (N=l 75 or 58.7%) and for the high (N=6 or 2.0%). The result for determine the difference of mental toughness level endurance runners between genders show that male low level (N=52 or 33.1%), moderate level (N=l0l or 65.3%), high level (N=4 or 2.5%) and for female low level (N=65 or 46%), moderate level (N=74 or 52.5%), high level (N=2 or 1.5%). The results finding showed there has a significant difference of mental toughness level between genders (p-value=0.038<0.05). Conclusion of this study showed that male endurance runners have a higher mental toughness level compare to the female endurance ruru1ers mental toughness level. Based on this observation, female endurance runners need more attention on development of their mental toughness.